ANALISIS KINERJA PENDIDIK DAN TENAGA KEPENDIDIKAN TK AISYIYAH BUSTANUL ATHFAL PANCOR: PENDEKATAN BALANCED SCORECARD - Fadma Rosita; M Rudi Gunawan Parozak (Berugak Baca, 2024)
This research has the aim of: measuring the level of performance of educators and teaching staff from a financial perspective and a customer satisfaction perspective, using a balanced scorecard approach. This type of research is descriptive research, which is combined with a qualitative approach. This research was conducted at Aisyiyah Bustanul Athfal Pancor Kindergarten. The subjects of this research are teachers and educational staff at this school. The results of this research are that in the performance analysis based on a financial perspective, a score of 13 out of a maximum score of 15 was obtained. This score is on a scale of 13 - 15 and is in the Very Good category. Financial performance from the economic aspect is included in the Economic category, financial performance from the effectiveness aspect is included in the Very Effective category, while from the efficient aspect, performance is included in the Efficient category. The results of the analysis carried out on performance from the perspective of internal and external customer satisfaction obtained a score of 7 (70%) out of a maximum score of 10. This score is on a scale of 68.01% -84% and is in the Satisfied category. The results of measuring the performance of the Balanced Scorecard for internal customers obtained a score of 14 (90%) out of a maximum score of 15 and is on a scale of 78.01% - 102% and is in the quite good category.